The Influence of Poster Media on Students' Narrative Writing Skills in Indonesian Language Learning from an Islamic Education Perspective - Winda Aprianti; Elvina Irma Eziztia; Rossi Delta Fitrianah; Bambang Irawan; Hengky Satrisno (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The purpose of this study was to determine the effect of using poster media on Narrative Writing Skills in Indonesian Language Learning for fifth grade students at SD Negeri 61 Bengkulu Selatan. The type of research used is quasi-experimental. Quasi-experimental itself can be interpreted as research that is close to a real experiment where it is impossible to strictly control or manipulate all relevant variables, while the method used in this study is a quantitative method. The population in this study were all students of class V. while the sample was class VA and VB. Data collection techniques used are observation, tests, and documentation. Data analysis techniques using statistics with the F test, and the r product moment test. The results of the study showed that there was an effect of using poster media on the narrative writing skills of fifth grade students at SD Negeri 61 Bengkulu Selatan. The t value is compared to dk = N1 + N2 2 = 17 + 17 2 = 32. With dk = 32, and if the error rate is set at 5%, then ttable = 1.81. Thus, tcount > ttable (6.010 > 1.81), which means that the working hypothesis (Ha) in this study is accepted, namely that there is an effect of using poster media on narrative writing skills in Indonesian language learning for class V students at SD Negeri